VD_FINDINFO HC / 2019 / 161 vom 25. Februar 2019 - VD Tribunal cantonal (2019)
MESURE PROVISIONNELLE, OBLIGATION D'ENTRETIEN, CONJOINT, ENFANT | 173 al. 3 CC, 176 al. 1 ch. 1 CC, 272 CPC (CH), 276 al. 1 CPC (CH)